Dyslipidemia and the Current State of Cardiovascular Disease: Epidemiology, Risk Factors, and Effect of Lipid Lowering - Liam R. Brunham; Eva Lonn; Shamir R. Mehta (2024)
Ischemic heart disease and stroke are the leading causes of death worldwide. Herein we review the burden, epidemiology, and risk factors for atherosclerotic cardiovascular disease (ASCVD). The focus of this review is on the current state of ASCVD in Canada, however, the findings regarding epidemiological trends are likely to be reflective of global trends, particularly in high-income countries, and the discussion regarding risk factors and lipid lowering is universally applicable. In Canada, the burden of death from ASCVD is second only to cancer deaths. There are major differences in disease burden related to sex, geography, and socioeconomic status. The major risk factors for ASCVD have been identified, although new and emerging risk factors are an active area of research. Recent developments such as polygenic risk scores provide potential to identify individuals at risk for ASCVD earlier in life and institute preventative measures. Dyslipidemia, and in particular elevated concentrations of low-density lipoprotein cholesterol and apolipoprotein B are a major cause of ASCVD. Therapies to lower low-density lipoprotein/apolipoprotein B levels are key components to treating and preventing ASCVD. Addressing the causal risk factors for ASCVD in a manner that comprehensively considers the clinical, social, and economic implications of prevention strategies will be essential to reduce the burden of ASCVD and improve outcomes for patients.